Age Interactions on Pain Sensitization in Patients With Severe Knee Osteoarthritis and Controls. Issue 12 (December 2017) - Petersen, Kristian K.; Arendt-Nielsen, Lars; Finocchietti, Sara; Hirata, Rogerio P.; Simonsen, Ole; Laursen, Mogens B.; Graven-Nielsen, Thomas
Abstract : Objectives: Widespread pressure hyperalgesia, facilitated temporal summation of pain (TSP), and impaired conditioned pain modulation (CPM) have been found in knee osteoarthritis (KOA) patients compared with controls and these parameters have further been suggested to be altered in the elderly. This study investigated the influence of age on pressure hyperalgesia, TSP, and CPM in patients with KOA and controls. Materials and Methods: One hundred thirty-three severe KOA patients and 50 age-matched and sex-matched asymptomatic controls were assessed by cuff algometry and handheld pressure algometry. Pain sensitivity was assessed around the head of the gastrocnemius muscle to identify mild pain detection threshold (MPDT) and pressure tolerance threshold (PTT). TSP was assessed by visual analogue scale scores of the pain evoked by 10 repetitive cuff stimulations. CPM was assessed as the difference in PTT before and during cuff-induced tonic arm pain. Pressure pain thresholds (PPTs) were assessed by handheld algometry at the tibialis anterior muscle. Two subgroups were analyzed in the age range below and above 65 years. Pearson correlations between age and pain parameters were applied. Results: Patients demonstrated reduced MPDT, PTT, and PPT ( P <0.01), facilitated TSP ( P <0.02), and a trend toward impaired CPM ( P =0.06) compared with controls. A negative correlation was found between MPDT, PTT, and PPT and age ( P <0.05) but no age-related association was found for TSP and CPM. Discussion: Pressure hyperalgesia was affected by age whereas dynamic pain mechanisms such as TSP and CPM were unaffected suggesting that these parameters are robust for a larger age range and reliable for long-term follow-up studies.